Existence of Weak Solutions for Fractional Integrodifferential Equations with Multipoint Boundary Conditions - Haide Gou; Baolin Li (International Journal of Differential Equations)
By combining the techniques of fractional calculus with measure of weak noncompactness and fixed point theorem, we establish the existence of weak solutions of multipoint boundary value problem for fractional integrodifferential equations.